2017
DOI: 10.1111/bjh.14693
|View full text |Cite
|
Sign up to set email alerts
|

Association between oxidative stress and vascular reactivity in children with sickle cell anaemia and sickle haemoglobin C disease

Abstract: Oxidative stress and haemolysis-associated nitric oxide (NO) depletion plays a crucial role in the development of vasculopathy in sickle cell anaemia (SS). However it remains unknown whether oxidative stress and haemolysis levels influence vascular function in patients with sickle haemoglobin C disease (SC). Microvascular response to heat (using Laser Doppler flowmetry on finger), oxidative stress biomarkers, NO metabolites, endothelin-1 and haematological parameters were compared between patients with SS and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 47 publications
4
17
0
1
Order By: Relevance
“…As previously discussed, oxidative stress is increased in SCD, both in plasma and RBC (15,82,(89)(90)(91)(92), with a further rise during painful vaso-occlusive crises (68). Through its effects on the membrane of RBCs (i.e., lipid peroxidation and protein oxidation) and caspase 3 activation (93, 94), oxidative stress is a key modulator of RBC rheological properties.…”
Section: Oxidative Stress and Rbcsmentioning
confidence: 98%
“…As previously discussed, oxidative stress is increased in SCD, both in plasma and RBC (15,82,(89)(90)(91)(92), with a further rise during painful vaso-occlusive crises (68). Through its effects on the membrane of RBCs (i.e., lipid peroxidation and protein oxidation) and caspase 3 activation (93, 94), oxidative stress is a key modulator of RBC rheological properties.…”
Section: Oxidative Stress and Rbcsmentioning
confidence: 98%
“…Indeed, patients with SCA suffer from chronic hemolytic anemia and repeated vaso-occlusive crises ( 1 ). Accumulating evidence suggests that chronic hemolysis, enhanced oxidative stress and decreased bioavailability of nitric oxide (NO) are at the origin of the vascular dysfunction observed in patients with SCA ( 2 4 ), which could be involved in the pathogenesis of several acute and chronic complications ( 3 ). In addition, heme released by red blood cells into the plasma could play a role in vascular dysfunction by promoting inflammation through the activation of Toll Like Receptor 4 (TLR4) ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Biswal et al [ 11 ] reported lower superoxide dismutase (SOD), catalase (CAT) and glutathione peroxidase (GPX) activities in SCA children compared to controls. Mockesch et al [ 7 ] found higher SOD activity in SCA than in healthy children and similar CAT and GPX activities in the two populations. Renoux et al [ 12 ] described higher SOD and lower GPX activities but similar CAT activity in a group of SCA children compared to a control group.…”
Section: Introductionmentioning
confidence: 97%
“…Oxidative stress is enhanced in SCA and would also play a major role in the pathophysiology of the disease by promoting red blood cell (RBC) damage, inflammation, and endothelial-vascular dysfunction [ 1 , 2 , 3 , 4 ]. Elevated advanced oxidation protein products (AOPP) and malondialdehyde (MDA) concentrations have been consistently reported in patients with SCA, both at a systemic or RBC level [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. As a consequence, it would be expected that RBC and plasma from patients with SCA exhibit decreased antioxidant capacities.…”
Section: Introductionmentioning
confidence: 99%